Do sheep-grazed pastures support insectivorous bat activity and bat species richness? - Florian Wiesinger; Marcela Suarez-Rubio (PLoS ONE, 2026)
Arable agriculture is usually associated with monoculture and the usage of pesticides, which jeopardize biodiversity and ecosystem processes. Grazing livestock can potentially benefit bats, however, most studies evaluate cattle, and it is unclear whether the results apply to grazing sheep. We assessed the effects of grazing sheep on insectivorous bat activity and species richness in southern Burgenland, Austria. We conducted acoustic surveys during the summer of 2019 on 49 pastures, which were in each case temporally divided into three categories (pre-grazed, grazed, and post-grazed). During the surveys, 20 of Burgenland’s 24 different bat species were detected. The most prevalent species was Pipistrellus pygmaeus . Small aerial insectivores showed significantly higher activity in grazed and post-grazed pastures compared to pre-grazed pastures, with no difference between grazed and post-grazed conditions. Frequent species (those occurring at ≥30% of sampled pastures) were more active in grazed than pre-grazed pastures but showed similar activity between pre-grazed and post-grazed pastures. At the species level, Nyctalus noctula activity was significantly higher in post-grazed compared to pre-grazed pastures. Overall bat activity, infrequent species activity, and species richness did not differ among grazing phases. Our results capture immediate responses during grazing and brief post-grazing resource pulses within days. Thus, comparisons with cattle should be cautious, as many cattle studies span weeks to months on larger, higher-biomass pastures. Apparent differences likely reflect timeframe, pasture size, stocking rate, and dung processes as much as livestock type, highlighting the need to consider livestock and management context when assessing bat responses and designing conservation-oriented grazing strategies.